Relational and algebraic methods in computer science : 17th International Conference, RAMiCS 2018, Groningen, The Netherlands, October 29-November 1, 2018, Proceedings /: 17th International Conference, RAMiCS 2018, Groningen, The Netherlands, October 29-November 1, 2018, Proceedings. (2018) - Unknown
No abstract available